Validating two-dimensional leadership models on three-dimensionally structured fish schools - Watts, I; Nagy, M; Holbrook, R; Biro, D; Burt De Perera, T (Royal Society, 2017)
dentifying leader-follower interactions is crucial for understanding how a group decides where or when to move, and how this information is transferred between members. Although many animal groups have a three-dimensional structure, previous studies investigating leader-follower interactions have often ignored vertical information. This raises the question whether commonly used two-dimensional leader-follower analyses can be used justifiably on groups that interact in three dimensions. To address this we quantified the individual movements of banded tetra fish (Astyanax mexicanus) within shoals by computing the three-dimensional trajectories of all individuals using a stereo-camera technique. We used these data firstly to identify and compare leader-follower interactions in two and three dimensions, and secondly to analyse leadership with respect to an individual’s spatial position in three dimensions. We show that for 95% of all pairwise interactions leadership identified through two-dimensional analysis matches that identified through three-dimensional analysis, and we reveal that fish attend to the same shoalmates for vertical information as they do for horizontal information. Our results therefore highlight that three-dimensional analyses are not always required to identify leader-follower relationships in species that move freely in three-dimensions. We discuss our results in terms of the importance of taking species’ sensory capacities into account when studying interaction networks within groups.